Auditory evoked cortical responses to frequency glides in subjects with retrocochlear hearing impairment. - Arlinger, S D (1983)
Auditory cortical responses evoked by stimulation with frequency glides of a continuous tone have been recorded from 44 subjects with intracranial tumours affecting auditory function. Response latencies obtained when stimulating the ear on the side of the tumour were different from the non-tumour ear as well as from groups with cochlear impairment and normal hearing. Tumours caused a reduction of a specific sensitivity to the frequency glide stimulation, affecting further processing of the dynamic change in tone frequency. The test appears to have diagnostic potential.